The Linguistics of Social Media: Unravelling the Digital Discourse - Bhamra, Veerpal; Sharma, Harsh (Journal of Advanced Research in English & Education, 2024)
Social media platforms have transformed the landscape of human communication, giving rise to a rich tapestry of linguistic phenomena. This journal article delves into the intricate interplay between language and digital culture, exploring the diverse linguistic features, communicative strategies, and sociocultural implications of social media discourse. Drawing on insights from linguistics, sociology, and the digital humanities, this study examines how language shapes and is shaped by the unique affordances of online platforms. Through a multidimensional analysis, this article sheds light on the evolving dynamics of communication in the digital age and highlights avenues for future research in the burgeoning field of social media linguistics.